Lifespan of long‐lived growth hormone receptor knockout mice was not normalized by housing at 30°C since weaning. Issue 5 (28th February 2020) - Fang, Yimin; McFadden, Samuel; Darcy, Justin; Hascup, Erin R.; Hascup, Kevin N.; Bartke, Andrzej
Abstract: Growth hormone receptor knockout (GHRKO) mice are remarkably long‐lived and have improved glucose homeostasis along with altered energy metabolism which manifests through decreased respiratory quotient (RQ) and increased oxygen consumption (VO2 ). Short‐term exposure of these animals to increased environmental temperature (eT) at 30°C can normalize their VO2 and RQ. We hypothesized that increased heat loss in the diminutive GHRKO mice housed at 23°C and the consequent metabolic adjustments to meet the increased energy demand for thermogenesis may promote extension of longevity, and preventing these adjustments by chronic exposure to increased eT will reduce or eliminate their longevity advantage. To test these hypotheses, GHRKO mice were housed at increased eT (30°C) since weaning. Here, we report that contrasting with the effects of short‐term exposure of adult GHRKO mice to 30°C, transferring juvenile GHRKO mice to chronic housing at 30°C did not normalize the examined parameters of energy metabolism and glucose homeostasis. Moreover, despite decreased expression levels of thermogenic genes in brown adipose tissue (BAT) and elevated core body temperature, the lifespan of male GHRKO mice was not reduced, while the lifespan of female GHRKO mice was increased, along with improved glucose homeostasis. The results indicate that GHRKO mice have intrinsic features that help maintain their delayed, healthy aging, and extended longevity at both 23°C and 30°C. Abstract : Chronic housing at 30°C of long‐lived growth hormone receptor knockout (GHRKO) mice since weaning did normalize the examined parameters of energy metabolism and glucose homeostasis. The lifespan of male GHRKO mice was not reduced, while the lifespan of female GHRKO mice was increased, along with improved glucose homeostasis. The results indicate that GHRKO mice have intrinsic features that help maintain their delayed, healthy aging, and extended longevity at both 23°C and 30°C.